Cover Picture: Hierarchical Hybrids of Mesoporous NiCo2O4 Needles/Graphene/Carbon Nanotubes with High Performance for Lithium Ion Batteries and Oxygen Reduction Reactions (ChemNanoMat 12/2016). Issue 12 (29th November 2016) - Yan, Yan; Liu, Yuqing; Ni, Weiyan; Wu, Jinyan; Liu, Mingkai; Liu, Tianxi
Abstract : Hierarchical NiCo2 O4 ‐graphene/carbon nanotube hybrids have been created by vertically anchoring NiCo2 O4 needles on conductive graphene/carbon nanotube films. The resulting materials exhibit porous structures, full exposure of active sites, and rapid electron transfer inside the hybrids, and can serve as high‐performance electrodes for both lithium‐ion batteries and oxygen reduction reactions. More information can be found in the Full Paper by M. Liu, T. Liu et al. onpage 1077 in Issue 12, 2016 (DOI:10.1002/cnma.201600259 ).